PERAN SIFAT KONSUMEN DAN FAKTOR SITUASIONAL TERHADAP IMPULSE BUYING (STUDI PADA KONSUMEN CV. ARLI SINGKAWANG) - B1021161038, Septi Purnama Sari (Jurnal Manajemen Update, 2020)
AbstractThis research is conducted to find out the effect of shopping enjoyment tendency, person?s situation, store environment, motivational activities by retailers, and product attributes toward the impulse buying in CV. Arli Singkawang. The method used in this research is associative, and the technique of data collecting used is questionaire. The population in this research is the all consumers that shop in CV. Arli Singkawang with 100 respondents. The sampling used in this research is non probability sampling accidental sampling and the tool is multiple regression analysis.The result of the data analysis shows that person?s situation, motivational activities by retailers, and product attributes significantly affect the impulse buying, while shopping enjoyment tendency and store environment does not significantly affect the impulse buying. The ability of those three variables in explaining the effect toward the impulse buying is 37,6% while the remaining 62,4% is explained by the other factors outside the research models. Keywords: shopping enjoyment tendency, person?s situation, store environment, motivational activities by retailers, product attributes, impluse buying DAFTAR PUSTAKAAdiputra, Eka. (2015). Perilaku Pembelian Tidak Terencana (Impulse Buying) di Pusat Perbelanjaan Modern di Surabaya. Vol.01 No.02 Afrianti, Ria. (2010). Pengaruh Atribut Supermarket terhadap Impulse Buying (Survei pada Supermarket di Kota Bandung). Jurnal Pendidikan Manajemen Bisnis. Vol. 9 No. 17, pp. 1-75 Amos, C., Holmes, G. R. And Keneson, W.c. (2014). A Mete-Analysis Of Consumer Impulse Buying. Journal of Retailing and Consumer Services, Vol. 21 No.2, pp. 86-97 Ardiyanto, Faizal. (2017). Pengaruh Positive Emotion, Time availability, dan Money Availability terhadap Impulse Buying Behavior Konsumen Mahasiswa pada Departement Store di Kota Yogyakarta. Jurnal Akuntansi dan Manajemen, Vol. 14 No. 1, pp. 850-862 Arnold, M. J. and Reynolds, K.E. (2003). Hedonic Shopping Motivations. Journal of Retailing, Vol 108 No. 2, pp. 72-178 Atulkar, S. And Kesari, B. (2018). Role Of Consumer Traits And Situational Factors On Impulse Buying: Does Gender Matter. International Journal of Retail & Distribution Management. Vol. 46 No. 4, pp. 386-405 Babin, B. J., Darden, W. R. and Griffin, M. (1994). Work and/or Fun: Measuring Hedonic and Utilitarian Shopping Value. Journal of Consumer Research, Vol. 20 No. 4, pp. 644-656 Badgaiyan, A.J. and Verma, A. (2015). Does Urge to Buy Impulsively Differ from Impulsive Buying Behaviour? Assessing The Impact Of Situational Factors. Journal of Retailing and Consumer Services, Vol. 22 No. 1, pp. 145-157 Baker, J., Parasuraman, A., Grewal, D. and Vos, G.B. (2002). The Influence Of Multiple Store Environment Cues On Perceived Merchandise Value and Patronage Intentions. Journal of Marketing, Vol. 66, pp. 120-141 Beatty, S.E. and Ferrell, M.E. (1998). Impulse Buying: Modeling Its Precursors. Journal of Retailing, Vol. 74 No. 2, pp. 169-191 Dalihade, M. P., Massie, J.D.D. dan Tielung, M.V.J. (2017). Pengaruh Potongan Harga dan Store Atmosphere terhadap Impulse Buying pada Matahari Departement Store Mega Mall Manado. Jurnal EMBA, Vol. 5 No. 3, pp. 3538-3549 Ghozali, I. (2011). Aplikasi Analisis Multivariate dengan SPSS. Semarang: penerbit Universitas Ponogoro Ghozali, I. (2013). Aplikasi Analisis Multivariat dengan Program IBM SPSS 21. Edisi 7. Semarang: Penerbit Universitas Ponogoro Gitosudarmo, Indriyo. (2014). Manajemen Pemasaran. Edisi kedua. Yogyakarta: BPFE Jones, M.A., Reynolds, K.E., Seungoog, W. And Beatty, S.E. (2003). The Product-Specific Nature Of Impulse Buying Tendency. Journal of business research, vol. 56 No. 7, pp. 505-511 Kharisma, Sandya & Sri Ardani. (2018). Pengaruh personality dan shop enjoyment terhadap impulse buying behavior yang dimediasi impulse buying tendency. E-Jurnal Manajemen, Vol. 7 No. 6, pp. 3320-3352 Kotler, Phillip and Armstrong, Gerry. (2012). Prinsip-Prinsip Pemasaran. Edisi 13. Jilid 1. Jakarta: Erlangga Kotler, Phillip and keller, K. L. (2009). Manajemen Pemasaran. Edisi 13, jilid 1. Jakarta : Erlangga Liao, S. L., Shen, Y. C. and Chu, C. H. (2009). The Effects of Sales Promotion Strategy, Product Appeal and Consumer Traits on Reminder Impulse Buying Behavior. International Journal of Consumer Studies, Vol. 33 No. 3, pp. 274-284 Marsha, L. R., and Dawson, S. (1992). A Consumer Values Orientation for Materialism and Its Measurement: Scale Development and Validitation. Journal of Consumer Research, Vol. 19, pp. 303-316 Maymand, Mohammad Mahmoudi and Mostafa Ahmadinejad. (2011). Impule Buying: The Role Of Store Environmental Stimulation And Situation Factors (An Empirical Inestigation). African Journal Business Management, Vol. 5(34), pp. 13057-13065 McGoldrick, P. J. (1982). How Unplanned Are Impulse Purchases?. Retail and Distribution Management, Vol. 10 No. 1, pp. 27-32 Mohan, G., Sivakumaran, B. and Sharma, P. (2013). Impact Of Store Environement On Impulse Buying Behaviour. European Journal of Service Marketing, Vol. 47 No. 10, pp. 1711-1732 Morissan. (2012). Metode Penelitian Survei. Jakarta: Premadenia Group Mowen, John. C and Minor, Michael. (2001). Perilaku Konsumen. Jakarta: Erlangga Nsairi, Z. B. (2012). Managing Browsing Experience in Retail Stores Through Perceived Value: Implications for Retailers. International Journal of Retail & Distribution Management, Vol. 40 No. 9, pp. 770-789 O?Cass, A. (2004). Fashion clothing consumption : antecedents and consequences of fashion clothing involvement. European Journal of Marketing, 388 (7), 69-82. Park, C. P., Iyer, E. S. and Smith, D. C. (1992). The Effects Of Situational Factors on in-Store Grocery Shopping Behavior: The Role Available for Shopping. Journal of Consumer Research, Vol. 15 No. 4, pp. 422-433 Peter, J.P. dan Olson, J.C. (2014). Perilaku Konsumen & Strategi Pemasaran. Edisi 9. Jakarta: Salemba Empat Pradana, A.E. dan Gede Suparna. (2016). Pengaruh Store Environment dan Impulse Buying Tendency Terhadap Urge To Buy Impulsively dan Impulse Buying Behavior. E-Jurnal Manajemen, Vol. 5 No. 7, pp. 4101-4131 Prasetya, Aries. dan Roharja, Sisilo Toto. (2016). Analisis Pengaruh Ketersediaan Uang dan Waktu, Lingkungan Toko, Nilai Belanja Hedonis, dan Emosi Positif Terhadap Pembelian Tak Terencana (Studi Kasus pada Pelanggan Lottemart di Kota Jakarta). Jurnal Manajemen, Vol. 5 No. 3, pp.1-11 Putri, A.S.K. dan Suharyono. (2017). Pengaruh Hedonic Shopping Motives dan Promosi Penjualan Terhadap Impulse Buying (Survei Pada Konsumen Matahari Departement Store Malang Town Square). Jurnal Administrasi Bisnis, Vol. 47 No. 2, pp. 145-153 Richins, M.L. (2011). Materialism, Transformation Expectaions, and Spending: Implications for Credit Use. Journal of Public Policy and Marketing, Vol. 30 No. 2, pp. 141-156 Rook, D.W. (1987). The Impulse Buying. Journal of Consumer Research, Vol. 14 No.2, 189-199. Simamora, Bilson. (2003). Memenangkan Pasar dengan Pemasaran Efektif dan Profitabel. Jakarta: Gramedia Pustaka Utama Sproles, G.B. and Kendall, E.L. (1986). A Methodology for Profiling Consumer?s Decision-making Styles. Journal of Consumer Affairs, Vol. 20. No. 2, pp. 267-279 Suarmaja, I.B.K., Wardana, Made. Dan Sukaatmadja, G.P. (2016). Pengaruh Atribut Produk Pakaian terhadap Web Browsing Hedonism dan Pembelian Impulsif. E-Jurnal Ekonomi dan Bisnis, Vol. 5 No. 12, pp. 4237-4270 Sugiyono. (2014). Metode Penelitian Bisnis. Bandung: Alfabeta. Sugiono. (2017). Metode Penelitian Bisnis Pendekatan Kuantitatif, Kualitatif, Kombinasi dan R&D. Bandung: Alfabeta Sujarweni, V. Wiratna. (2015). Metode Penelitian Bisnis & Ekonomi. Yogyakarta: Pustakabarupress Suryani dan Hendryadi. (2015). Metode Riset Kuantitatif Teori dan Aplikasi pada Penelitian Bidang Manajemen Dan Ekonomi Islam. Jakarta: Prenadamedia Group Tjantoko, L. E. dan Japarianto, Edwin. (2015). Analisa Pengaruh Promosi dan Hedonic Motivation terhadap Impulse Buying di Rons?s Lavoratory Galaxi Mall Surabaya. Jurnal Manajemen Pemasaran, Vol. 3 No. 1, pp. 1-7 Utami, C.W. (2010). Manajemen Ritel: Strategi dan Implementasi Operasional Bisnis Ritel Modern di Indonesia. Edisi 2. Jakarta: Salemba Empat. Verplanken, B. and Herabadi, A. (2001). Individual Differences in Impulse Buying Tendency: Felling and No Thinking. European Journal of Personality, Vol. 15 No. 1, pp. 71-83 Widodo, Siswo Widhi Sofyan. (2016). Pengaruh Shopping Enjoyment Tendency dan Impulsive Buying Tendency Terhadap Impulsive Buying Behaviour di Carrefour Kota Mojokerto. Jurnal Ilmiah Mahasiswa FEB Universitas Brawijaya, Vol. 4 No. 2. Website :https://databoks.katadata.co.id/datapublish/2019/03/27/2018-terdapat-1131-toko-modern-di-indonesia diakses tanggal 03 Oktober 2019 http://www.barantum.com/blog/tren-bisnis-ritel diakses tanggal 28 Oktober 2019 https://ekonomi.bisnis.com/read/20190107/12/876089/2019-bisnis-ritel-modern-ditarget-tumbuh-10 diakses tanggal 28 Oktober 2019 https://Sulisfashion214.wordpress.com/2016/12/02/definisi-dan-pengertian-fashion/ diakses tanggal 13 desember 2019